Structural parameters effect on the electrical and electroluminescence properties of silicon nanocrystals/SiO2 superlattices. (15th April 2015) - López-Vidrier, J; Berencén, Y; Hernández, S; Mundet, B; Gutsch, S; Laube, J; Hiller, D; Löper, P; Schnabel, M; Janz, S; Zacharias, M; Garrido, B
Abstract: The effect of the oxide barrier thickness ( t SiO2 ) reduction and the Si excess ([Si]exc ) increase on the electrical and electroluminescence (EL) properties of Si-rich oxynitride (SRON)/SiO2 superlattices (SLs) is investigated. The active layers of the metal–oxide–semiconductor devices were fabricated by alternated deposition of SRON and SiO2 layers on top of a Si substrate. The precipitation of the Si excess and thus formation of Si nanocrystals (NCs) within the SRON layers was achieved after an annealing treatment at 1150 °C. A structural characterization revealed a high crystalline quality of the SLs for all devices, and the evaluated NC crystalline size is in agreement with a good deposition and annealing control. We found a dramatic conductivity enhancement when the Si content is increased or the SiO2 barrier thickness is decreased, due to a larger interaction of the carrier wavefunctions from adjacent layers. EL recombination dynamics were studied, revealing radiative recombination decay times of the order of tens of microseconds. Lower lifetimes were found at higher [Si]exc, attributed to exciton confinement delocalization, whereas intermediate barrier thicknesses present the slowest decay. The electrical-to-light conversion efficiency increases monotonously at thicker barriers and smaller Si contents. We ascribe these effects mainly to free carriers, which enhance carrier transport through the SLs while strongly quenching light emission. Finally, the combination of the different results led us to conclude that t SiO2  ∼ 2 nm and [Si]exc from 12 to 15 at% are the ideal structure parameters for a balanced electro-optical response of Si NC-based SLs.